2020
DOI: 10.1590/1414-431x20209798
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA TUG1 promotes proliferation and differentiation of osteoblasts by regulating the miR-545-3p/CNR2 axis

Abstract: Osteoblast differentiation is an effective way to promote bone formation. Long non-coding RNA taurine upregulated 1 (TUG1) has been identified as a crucial modulator of multiple biological processes. This study was designed to investigate the function of TUG1 in the proliferation and differentiation of osteoblast precursor cells hFOB1.19. In this study, we found that TUG1 promoted hFOB1.19 cell proliferation, while TUG1 knockdown hindered cell proliferation. TUG1 and cannabinoid receptor 2 (CNR2) were upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“… 25 To confirm whether miR‐34a is regulated by lncRNA, the lncRNAs that could interact with miR‐34a were predicted by StarBase database. Among the candidates, lncRNA TUG1, which is involved in regulating osteoblast proliferation and differentiation, 26 is an important potential target. The qRT‐PCR results demonstrated that lncRNA TUG1 levels were significantly increased in response to FSS in MC3T3‐E1 cells (Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 To confirm whether miR‐34a is regulated by lncRNA, the lncRNAs that could interact with miR‐34a were predicted by StarBase database. Among the candidates, lncRNA TUG1, which is involved in regulating osteoblast proliferation and differentiation, 26 is an important potential target. The qRT‐PCR results demonstrated that lncRNA TUG1 levels were significantly increased in response to FSS in MC3T3‐E1 cells (Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, lncRNA TUG1 was up‐regulated in osteoblasts cultured under FSS, and lncRNA TUG1 could enhance osteoblast proliferation and inhibit osteoblast apoptosis. Hao et al 26 reported that lncRNA TUG1 sponged miR‐545‐3p to up‐regulate CNR2, facilitating osteoblast proliferation and differentiation in hFOB1.19 cells. Liu et al 41 discovered that lncRNA TUG1 accelerated osteoblast proliferation by Wnt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-545-3p dysregulation has been reported in diverse cancers. Shi et al reported that miR-545-3p was downregulated in epithelial ovarian cancer (35); Hao et al showed that miR-545-3p inhibits the proliferation and differentiation of osteoblasts (36); and Zhong et al reported that miR-545-3p functions as a tumor suppressor in endometrial carcinoma (37). Furthermore, some studies indicate that miR-545-3p may be the target of circRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Precious research has shown that miR-545-3p has pivotal roles in the regulating cellular behaviors, such as proliferation, differentiation and migration. 30 , 31 It has recently been identified as a cancer-related miRNA for several cancers. For example, Changjun et al declared that miR-545-3p was highly expressed in hepatocellular carcinoma tissues and cells, and miR-545-3p inhibition limited hepatocellular carcinoma cell proliferation and metastasis via regulating MT1M.…”
Section: Discussionmentioning
confidence: 99%